LncRNA ZEB1-AS1/miR-1224-5p / MAP4K4 axis regulates mitochondria-mediated HeLa cell apoptosis in persistent Chlamydia trachomatis infection. Issue 1 (31st December 2022) - Luo, Fangzhen; Wen, Yating; Zhao, Lanhua; Su, Shengmei; Lei, Wenbo; Chen, Lili; Chen, Chaoqun; Huang, Qiulin; Li, Zhongyu
ABSTRACT: Persistent infection of Chlamydia trachomatis is thought to be responsible for the debilitating sequelae of blinding trachoma and infertility. Inhibition of host cell apoptosis is a persistent C. trachomatis infection mechanism. ZEB1-AS1 is a long non-coding RNA (lncRNA), which was up-regulated in persistent C. trachomatis infection in our previous work. In this study, we investigated the role of ZEB1-AS1 in persistent infection and the potential mechanisms. The results showed that ZEB1-AS1 was involved in the regulation of apoptosis, and targeted silencing of ZEB1-AS1 could increase the apoptosis rate of persistently infected cells. Mechanically, interference ZEB1-AS1 caused an apparent down-regulation of the Bcl-2/Bax ratio and the repression of the mitochondrial membrane potential with the remarkable release of cytochrome c, resulting in the significant elevation level of caspase-3 activation. Meanwhile, the luciferase reporter assay confirmed that ZEB1-AS1 acted as a sponge for miR-1224-5p to target MAP4K4. The regulatory effect of miR-1224-5p/MAP4K4 on persistent infection-induced antiapoptosis was regulated by ZEB1-AS1. In addition, ZEB1-AS1 inhibited the apoptosis of Chlamydia -infected cells by activating the MAPK/ERK pathway. In conclusion, we found a new molecular mechanism that the ZEB1-AS1/miR-1224-5p/MAP4K4 axis contributes to apoptosis resistance in persistent C. trachomatis infection. This work may help understand the pathogenic mechanisms of persistent C. trachomatis infection and reveal a potential therapeutic strategy for its treatment. GRAPHICAL ABSTRACT: